Modulating Endoplasmic Reticulum Stress in Gastrointestinal Cancers: Insights from Traditional Chinese Medicine - Qinyi Li; Xiaohong Zhao; Huan Yang; Xiaolong Zhu; Xinbing Sui; Jiao Feng (Pharmaceuticals, 2024)
Endoplasmic reticulum (ER) stress and the unfolded protein response (UPR) play critical roles in tumorigenesis, cancer progression, and drug resistance. Persistent activation of the ER stress system enhances the survival capacities of malignant tumor cells, including increased proliferation, invasion, and resistance to treatment. Dysregulation of ER function and the resultant stress is a common cellular response to cancer therapies and may lead to cancer cell death. Currently, growing evidence suggests that Traditional Chinese medicine (TCM), either as a monotherapy or in combination with other treatments, offers significant advantages in preventing cancer, inhibiting tumor growth, reducing surgical complications, improving drug sensitivity, and mitigating drug-induced damage. Some of these natural products have even entered clinical trials as primary or complementary anticancer agents. In this review, we summarize the anticancer effects of TCM monomers/natural products on the gastrointestinal (GI) tumors and explore their mechanisms through ER stress modulation. We believe that ongoing laboratory research and the clinical development of TCM-based cancer therapies hold considerable potential for advancing future cancer treatments.